Web based decision support system for computer buyers using Bayesian’s technique - Ali, Selamat; Tan, Li Kim (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.